Multiple Lesion of the Colon and Ileocaecal Valve in Patient with Colitis Tuberculosis with Positive Bacilli Examination in the Stool - Ali Imron Yusuf; Ari Fahrial Syam; Marcellus Simadibrata; Achmad Fauzi (The Indonesian Society for Digestive Endoscopy, 2009)
It is sometimes hard to establish the diagnosis of colon tuberculosis because the ulceration features on ileocaecal valve and caecum are not specific. Moreover, biopsy of lesion area can only provide 60-80% detection. The lesions usually include linear or transversal ulcer, nodule, abnormal form of ileocaecal valve and caecum, inflammatory polyp and irregular multiple fibrous bands. We report a case of colon tuberculosis in a 32-years-old woman with giant ulcer and pseudopolyps at ileus terminalis and ileocaecal junction detected by colonoscopy, in addition to multiple ulcers along the colon, starting from rectum to ascending colon. By fecal examination, positive Acid Fast Test (AFT) result was found and by chest X-ray, tuberculosis features were also found. Keywords: tuberculosis colitis, multiple ulcers in colon, giant ulcer, pseudopolyp, fecal AFT, colonoscopy